The Impact of Blood Cupping (Al-Hijama) on Serum Creatinine and Uric Acid Levels in Patients from Hadhramout, Yemen - Sumaidea, Saleh Bin; Hassan, Hassan Pyar Ali; Bakaduem, Adnan Ali; Almashjari, Abdulrahman Omar; Bashumail, Abdullah Shamlan; Blhamed, Mohammed Saeed (Chimica et Natura Acta, 2023)
Cupping is a wonderful healing tool that has been employed for hundreds of years by numerous traditional folklore practitioners. Cupping treats many diseases including eliminating blood pollutants like uric acid and creatinine. The aim of this study to evaluate the impact of cupping on blood pressure, uric acid concentration, and creatinine levels. Sixty (60) random patient between the ages of (20 -70) years were selected, the blood samples were collected before cupping and after cupping for the evaluation. The result showed that the levels of creatinine and uric acid decreased significantly (p < 0.05) after cupping for both creatinine and uric acid. Moreover, the study showed that blood pressure decreased significantly (p < 0.05) after cupping. The result concluded that cupping has positive impact on health by modulating creatinine, uric acid blood levels and decreasing blood pressure.